2018
DOI: 10.1155/2018/2032461
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hierarchical Clustering Algorithm Based on Density Peaks for Complex Datasets

Abstract: Clustering aims to differentiate objects from different groups (clusters) by similarities or distances between pairs of objects. Numerous clustering algorithms have been proposed to investigate what factors constitute a cluster and how to efficiently find them. The clustering by fast search and find of density peak algorithm is proposed to intuitively determine cluster centers and assign points to corresponding partitions for complex datasets. This method incorporates simple structure due to the noniterative l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…For example, [16] applied the concept of heat diffusion and [17] employed the potential entropy of the data field to assist in setting the radius . Also, many studies suggested using k nearest neighbors to define density, instead of using the radius [18][19][20][21]. Furthermore, [22] suggested calculating two kinds of densities, one based on k nearest neighbors and one based on local spatial position deviation, to handle datasets with mixed density clusters.…”
Section: Variants Of Dpcmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, [16] applied the concept of heat diffusion and [17] employed the potential entropy of the data field to assist in setting the radius . Also, many studies suggested using k nearest neighbors to define density, instead of using the radius [18][19][20][21]. Furthermore, [22] suggested calculating two kinds of densities, one based on k nearest neighbors and one based on local spatial position deviation, to handle datasets with mixed density clusters.…”
Section: Variants Of Dpcmentioning
confidence: 99%
“…To resolve this problem, [23] proposed a comparative technique to choose the density peaks, [24] estimated density dips between points to determine the number of clusters, and [25] applied data detection to determine density peaks automatically. In [21], the optimal number of clusters was extracted from the results of hierarchical clustering. Furthermore, it may be more suitable for some datasets to locate a cluster by more than one density peak [26,27].…”
Section: Variants Of Dpcmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be more or less supervised, notably on the number of clusters k, which is required for instance in the k-means method [53][54][55][56]. Cluster density has been developed to partition the initial graph into smaller ones, depending on local density values of each cluster [57][58][59][60][61]. Cut size-based measures allow the quantification of the dependence of a subgraph to the rest of the graph [62,63], with several indices, like for instance Dunn index [64], Davies-Boulding index [65], Xie and Beni's validity index [66], and Bezdek's partition coefficient and partition entropy [67,68].…”
Section: Related Workmentioning
confidence: 99%
“…Clustering algorithms group objects that are similar to each other in clusters. 1 Different clustering algorithms have been developed and applied to different data sets of very varied fields (medical databases, images, etc. ).…”
Section: Introductionmentioning
confidence: 99%